(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article addresses the relationship between the exercise of the judicial function and Artificial Intelligence, analyzing it from a twofold perspective. On the one hand, in fact, the use of AI technologies in the judicial system seems to highlight ancient issues and, on the other hand, raises new criticalities but it also opens to possible benefits.